2019
DOI: 10.1002/ece3.4902
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation and seasonality drive bird feeder use during winter in a Mediterranean climate

Abstract: Purposeful provisioning of food to wild animals is a widespread and growing activity that has the potential to impact populations and communities. Nevertheless, studies assessing use of recreational feeders by free‐living birds during winter are surprisingly rare and largely limited to regions with continental climates characterized by freezing temperatures and snow cover. In contrast, there is little information available regarding bird use of feeders within warmer climates during winter, despite widespread r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…We also recorded body mass, right tarsus length and flattened right wing chord for each individual at its initial capture; body mass was again measured at the time when treatments were applied to each bird which allowed us to compare body mass of birds assigned to different treatments. Given extensive individual variation in feeder use by unmanipulated chickadees in our study system (Lajoie et al 2019), we began recording feeder visitation data in January 2017 to obtain pre-treatment data that allowed us to control for individual differences in feeder use. Following this pre-treatment period we conducted trapping sessions at all feeders across a five-week period (25 January-2 March 2017) to recapture as many previously banded chickadees as possible.…”
Section: Chickadee Capture and Taggingmentioning
confidence: 99%
“…We also recorded body mass, right tarsus length and flattened right wing chord for each individual at its initial capture; body mass was again measured at the time when treatments were applied to each bird which allowed us to compare body mass of birds assigned to different treatments. Given extensive individual variation in feeder use by unmanipulated chickadees in our study system (Lajoie et al 2019), we began recording feeder visitation data in January 2017 to obtain pre-treatment data that allowed us to control for individual differences in feeder use. Following this pre-treatment period we conducted trapping sessions at all feeders across a five-week period (25 January-2 March 2017) to recapture as many previously banded chickadees as possible.…”
Section: Chickadee Capture and Taggingmentioning
confidence: 99%
“…Over the last two decades, the use of passive integrated transponder (PIT) tags has increased dramatically (Bridge et al., 2019). In ornithological research, radio‐frequency identification (RFID) devices are often placed at discreet locations, such as feeders or nest boxes, that PIT‐tagged birds will repeatedly visit (Johnson et al., 2013; Lajoie et al., 2019). PIT tags and RFID devices have enabled a variety of research questions to be tackled on topics including foraging behavior (Lajoie et al., 2019; Moiron et al., 2018), movement ecology (Bailey et al., 2018; Matechou et al., 2015), social networks (Brandl et al., 2021; Evans et al., 2018; Firth et al., 2015), reproductive ecology (Schlicht & Kempenaers, 2015; Schuett et al., 2012; Zangmeister et al., 2009), and physiology (Skold‐Chiriac et al., 2015; Whitfield et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have evaluated the effects of PIT tags on small passerine birds and found no evidence for any adverse effects (Table 1). Results such as these have led to a widespread adoption of PIT tags for field studies in small birds, including Black‐capped Chickadees (circa 10–12 g) (Bailey et al., 2018; Evans et al., 2018; Lajoie et al., 2019) and even hummingbirds (<4 g) (Hou et al., 2015). However, while the study in hummingbirds demonstrated that they could be tracked effectively with PIT tags, the study did not compare survival or body condition relative to birds that did not receive implants (Hou et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild bird feeding is one of the most common forms of wildlife interaction in the world (1)(2)(3)(4). It is particularly popular in developed countries with birds being fed at up to 75% of people's homes (2,(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%